Consumer preferences for aquaponics: A comparative analysis of Australia and Israel. (1st March 2020) - Greenfeld, Asael; Becker, Nir; Bornman, Janet F.; dos Santos, Maria José; Angel, Dror
Abstract: Aquaponics, the combined rearing of fish and hydroponic horticulture, has great potential for sustainable food production. Despite increasing research and investments in commercial scale systems, aquaponics is not yet a successful industry and most businesses report negative returns. Aquaponic produce is thought to contain added value to the consumer, and the environment. As most consumers are unaware of aquaponics and their benefits, little is known of its potential market. The present study addresses this gap by analysing willingness to consume aquaponic produce at different price levels in Israel and Australia. We used econometric tools to study the effects of pricing and other factors on revenues in each country. Cluster analysis was used to define groups of potential consumers. The results indicate that 17–30% of the population in both Israel and Australia would prefer to consume aquaponic produce once informed of their added value. Revenues at a given premium would be higher in Israel than in Australia, and higher for a leafy green, than for fish. Different segments of the population differed in their willingness to consume aquaponic produce, as well as in their stated motivations when purchasing food. Conclusions highlight the importance of case-specific research on consumer preferences and economic considerations preceding commercial investment in aquaponics. Highlights: Commercial aquaponics is restricted by insufficient economic development. Israeli and Australian consumers are willing to pay a premium for aquaponic produce. Assessing aquaponics price sensitivity depends on both culture and product. Maximising revenues calls for price decrease in Australia and increase in Israel.